Hepatitis B virus infection in children and adolescents. (June 2019) - Indolfi, Giuseppe; Easterbrook, Philippa; Dusheiko, Geoffrey; Siberry, George; Chang, Mei-Hwei; Thorne, Claire; Bulterys, Marc; Chan, Po-Lin; El-Sayed, Manal H; Giaquinto, Carlo; Jonas, Maureen M; Meyers, Tammy; et al.
Summary: Hepatitis B virus (HBV) infection is a major cause of acute and chronic liver disease and associated morbidity and mortality worldwide. Vertical (mother-to-child) and horizontal early childhood transmission are the main routes of HBV transmission and are responsible for most chronic infections, including among adults who bear the greatest burden of morbidity and mortality. Universal hepatitis B immunisation at birth and in infancy is the key strategy for global elimination of HBV infection, and has been highly effective in reducing new vertical infections. However, global progress in scale-up of HBV testing and treatment has been slow in adults and children. In this Series paper, we summarise knowledge on the epidemiology, natural history, and treatment of chronic HBV infection in adolescents and children, and we highlight key differences from HBV infection in adults. The estimated global prevalence of HBV infection in children aged 5 years or younger is 1·3%. Most children are in the high-replication, low-inflammation phase of infection, with normal or only slightly raised aminotransferases; cirrhosis and hepatocellular carcinoma are rare. Although entecavir is approved and recommended for children aged 2–17 years, and tenofovir for those aged 12–18 years, a conservative approach to treatment initiation in children is recommended. Key actions to address current policy gaps include: validation of non-invasive tests for liver disease staging; additional immunopathogenesis studies in children with HBV infection; long-term follow-up of children on nucleoside or nucleotide analogue regimens to inform guidance on when to start treatment; evaluation of different treatment strategies for children with high rates of HBV replication; and establishment of paediatric treatment registries and international consortia to promote collaborative research.